Posterior lingual gestures and tongue shape in Mangetti Dune !Xung clicks. (March 2016) - Miller, Amanda L.
Abstract: Clicks differ from pulmonic stops in that, in addition to containing lingual gestures that shape the filtering mechanism of the vocal tract, they also contain lingual "rarefaction gestures" that form the source of the lingual ingressive airstream. The current study uses mid-sagittal lingual ultrasound imaging to investigate (1) overall tongue shape, (2) tongue dorsum and root positions, and (3) dynamic rarefaction gestures involving the tongue dorsum and root, in the four coronal click types recognized by the IPA. The study provides quantitative evidence that the four click types differ in overall tongue shape. Additionally, results show that the palatal click has a farther back dorsal constriction than the three pre-palatal clicks, and the tongue root is raised and bunched in the upper pharynx in one variant of the palatal click, but involves retraction of the tongue root proper in the lower pharynx in the alveolar click. A second variant of the palatal click involves posterior gestures more similar to those found in the alveolar click. Results provide evidence that the kinematics of the posterior part of the tongue are important in describing click production, and shed light on synchronic and diachronic sound patterns involving the palatal click in Kx'a languages. Highlights: Palatal clicks differ from pre-palatal clicks in their tongue dorsum and root positions and shapes. The tongue root is raised and bunched in palatal clicks, but retracted into the mid pharynx in alveolar and lateral clicks. Tongue root movement during dental click production varies between little movement, minor retraction, and minor advancement. Tongue root raising seems to be compatible with front vowels, unlike tongue root retraction into the mid or lower pharynx.